Systematic Review: The Covid-19 Pandemic Effects on Maternal Anxiety During Pregnancy - Niken Bayu Argaheni (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Background: Anxiety is a common response to any stressful situation. Pregnant women are more likely to catch viral illnesses, and the Coronavirus can cause stress and anxiety in pregnant women in different parts of the world. The purpose of this study was to determine the effect of the Covid-19 pandemic on maternal anxiety during pregnancy.Method: Systematic review using the database: Google Scholar. The search results that meet the criteria are then analyzed for articles.Result: The saturation of mass media and social media with news related to COVID-19 and the dissemination of information in it provides a climate of fear, uncertainty and anxiety, about the present and the future. This will be magnified for pregnant women today who, even without a pandemic, generally pregnant women experience feelings of uncertainty and anxiety related to childbirth, childbirth, the presence of a baby and the care of a newborn.Conclusion: Pregnant women have a greater psychological impact as well as higher anxiety during the COVID-19 pandemic. Identification of pregnant women who are at high risk of anxiety that occurs during the Covid-19 pandemic is important so that health workers can suggest early psychological intervention and prevent some complications related to stress in pregnancy.